Solid electrolyte and preparation method thereof

Through isopropyl alcohol ball milling and double-layer crucible sintering method, the problems of grain coarsening and lithium volatilization in the preparation of garnet-type solid electrolytes were solved, and the preparation of solid electrolytes with high density and high ionic conductivity was achieved, which improved battery safety and ion transmission efficiency.

CN120736896APending Publication Date: 2025-10-03NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510950522.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

In the existing garnet-type solid electrolyte preparation process, the high-temperature solid-phase method leads to grain coarsening, insufficient density and lithium volatilization, affecting the ion transmission efficiency.

Method used

Isopropyl alcohol is used as the ball milling medium, combined with the double-layer crucible sintering method and the layered electrolyte sheet coating method. By refining the grains, improving the density, and inhibiting lithium volatilization, a MgO-Al2O3 double-layer crucible is used to enhance the sealing and sintering efficiency.

Benefits of technology

A solid electrolyte with high lithium ion conductivity and excellent chemical stability was prepared, with increased grain density, improved ion transfer efficiency, stable lithium content, and optimized conduction channel smoothness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120736896A_ABST
    Figure CN120736896A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte and a preparation method thereof, and the preparation method comprises the following steps: adding isopropanol into a raw material for preparing a tantalum-doped solid electrolyte or an aluminum-doped solid electrolyte as a ball-milling agent, carrying out ball milling, drying the ball-milled powder to obtain dry mixed powder, putting the dry mixed powder into an MgO crucible, and sintering to obtain the solid electrolyte. Adding isopropanol into the sintered product, carrying out ball milling again, drying, and screening to obtain solid electrolyte mother powder; tabletting the solid electrolyte mother powder to obtain a solid electrolyte green sheet; 2-4 solid electrolyte green sheets are coated with the solid electrolyte mother powder layer by layer from bottom to top in an MgO-Al2O3 double-layer crucible by adopting a coating method, the solid electrolyte mother powder is used for capping, and a layered coating is obtained; and sintering the layered coating, and then carrying out segmentation, grinding and polishing to obtain the solid electrolyte, according to the method provided by the invention, crystal grains and crystal grain density are refined, lithium element volatilization is avoided, and the ion transmission efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, in particular to a solid electrolyte and a preparation method thereof. Background Art

[0002] Garnet-type solid electrolytes (such as Li7La3Zr2O 12 LLZO) due to its high lithium ion conductivity (up to 3×10 -4 S cm -1 )‌, wide electrochemical window (>5Vvs.Li / Li + ) and excellent chemical stability (compatible with lithium metal), it is regarded as a core electrolyte candidate material for all-solid-state batteries‌.

[0003] While garnet-type electrolytes have slightly lower ionic conductivity than sulfide electrolytes, they offer superior thermal stability (high temperature resistance > 500°C) and are less prone to decomposition in air, making them more suitable for large-scale production. Furthermore, their high mechanical strength (Young's modulus > 150 GPa) effectively inhibits lithium dendrite penetration, improving battery safety.

[0004] However, the current preparation of garnet-type electrolytes relies primarily on high-temperature solid-phase methods (sintering temperatures > 1200°C). This process can lead to problems such as grain coarsening, insufficient density, and lithium volatilization, which severely impact ion transport efficiency. Therefore, addressing the challenges of existing garnet-type electrolyte preparation methods, developing a solid-state electrolyte preparation method is of great significance. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a solid electrolyte and a preparation method thereof, aiming to solve the problems raised in the technical background. The solid electrolyte preparation method refines the grains, improves the density of the electrolyte sheet, avoids the volatilization of lithium elements, and improves the ion transmission efficiency.

[0006] To solve the above technical problems, the present invention provides a method for preparing a solid electrolyte, comprising the following steps: Isopropyl alcohol is added as a ball milling agent to raw materials for preparing a tantalum-doped solid electrolyte or an aluminum-doped solid electrolyte, and the ball milling is performed. The ball milled powder is dried to obtain a dry mixed powder. The dry mixed powder is placed in an MgO crucible for sintering. Isopropyl alcohol is added as a ball milling agent to the sintered product, and the product is ball milled again, dried, and sieved to obtain a solid electrolyte mother powder. Pressing the prepared solid electrolyte mother powder into tablets to obtain solid electrolyte green sheets; In a MgO-Al2O3 double-layer crucible, the solid electrolyte mother powder is coated layer by layer on 2 to 4 solid electrolyte green sheets from bottom to top by using the coating method, and the top is sealed with the solid electrolyte mother powder to obtain a layered coating; The layered coating is sintered, divided after sintering, and then ground and polished to obtain a solid electrolyte; The inner layer of the MgO-Al2O3 double-layer crucible is a porous MgO crucible, and the outer layer of the double-layer crucible is an Al2O3 crucible.

[0007] Isopropyl alcohol was chosen as the milling medium because the isopropyl group in its molecular structure is more hydrophobic. Furthermore, its volatility is slightly lower than that of ethanol, which reduces solvent loss during the milling process. Compared to other solvents, isopropyl alcohol is a secondary alcohol, and its -OH group is less acidic and electrophilic than methanol and ethanol. Steric hindrance makes it more difficult for protons to insert into the LLZTO (tantalum-doped solid electrolyte) backbone, significantly reducing the proton exchange rate. As a low-viscosity liquid, isopropyl alcohol fills the gaps between the milling beads and the particles. When the milling beads collide, the liquid medium evenly distributes the impact force to the particle surface, preventing localized stress concentrations that could disrupt the crystal structure.

[0008] The effects of using isopropyl alcohol ball milling: 1. Reduce surface energy, that is, isopropyl alcohol molecules are adsorbed on the surface of raw material particles to form a solvation layer of about 2nm~5nm. When the particles are close, a steric effect is generated, which reduces particle agglomeration and prevents the crushed particles from re-bonding. 2. Promote dispersion, that is, by wetting the gaps between particles, weakening the van der Waals force between particles, and enhancing the mechanical grinding effect. 3. Control particle size distribution, by reducing the impact peak energy and inhibiting cold welding, making the crushing-re-bonding balance more stable and the final particle size distribution narrower. 4. Inhibit proton exchange. IPA has moderate polarity and weak proton donor ability, which can significantly inhibit Li + / H + Exchange and Li dissolution are particularly important for powders that are prone to Li loss, such as LLZTO (tantalum-doped solid electrolyte).

[0009] Preferably, 10 to 20 large ball milling beads with a diameter of 10 mm to 14 mm, 40 to 80 small ball milling beads with a diameter of 4 mm to 8 mm, and the raw materials for preparing the solid electrolyte are placed in a ball milling jar, and isopropyl alcohol is used as the ball milling medium for 5 h to 15 h.

[0010] Large 10mm-14mm beads are used for ball milling because they have a large mass, generate high kinetic energy during mill rotation, and effectively crush coarse particles. A small number of 10-20 large beads form a "skeleton" structure within the mill, preventing excessive accumulation of smaller 4mm-8mm beads. This ensures uniform distribution of the beads and improves energy transfer efficiency. Smaller beads fill the gaps between the larger beads, increasing overall fill density and effectively transferring collision energy to the powder rather than dissipating it between the beads. This creates a "multi-stage crushing" system—larger beads crush larger particles, while smaller beads continue to refine them to the submicron level, making the grinding process more efficient.

[0011] Preferably, the dried powder is sintered at a sintering temperature of 700° C. to 1000° C. for 8 h to 12 h at a heating rate of 2° C. / min to 5° C. / min.

[0012] During the sintering process, the raw materials used to prepare solid-state electrolytes undergo a transition from a low-temperature tetragonal phase to a high-temperature cubic phase. A slow heating rate (<2°C / min) prolongs the phase transition and leads to abnormal grain growth. A fast heating rate (>5°C / min) causes internal stress and microcracks due to the delayed phase transition. Too low a temperature prevents the complete cubic phase transition, while too high a temperature can result in significant lithium loss.

[0013] Preferably, the conditions for tableting the solid electrolyte mother powder to obtain the solid electrolyte sheet are: 1.0 g to 1.3 g of the mother powder is pressed under a pressure of 200 MPa to 400 MPa for 5 min to 6 min to obtain the solid electrolyte sheet.

[0014] The solid electrolyte sheet is pressed at a pressure of 200-400 MPa because higher pressures promote closer packing of the solid electrolyte sheet powder particles, thereby increasing the initial density of the compact. Reduced interparticle spacing enhances interparticle contact, facilitating material migration during the subsequent sintering process. However, excessively high pressures can easily introduce stress concentration zones within the powder, leading to cracks within and on the surface of the electrolyte sheet after the external force is removed.

[0015] Preferably, the mass of each layer of solid electrolyte mother powder wrapped solid electrolyte sheet is 1.0 g to 2.5 g.

[0016] Garnet-type solid electrolytes (such as Li 6.5 La3Zr 1.5 Ta 0.5 O 12During sintering, lithium volatilization can easily lead to compositional deviations. A mother powder mass of 1.0 g to 2.5 g per layer creates a saturated Li₂O atmosphere, preventing further decomposition of the mother powder and electrolyte sheet. If the mass is less than 1.0 g, the mother powder provides an insufficient lithium source, resulting in a large lithium concentration gradient within the electrolyte sheet, prone to compositional inhomogeneity and the formation of impurities in the electrolyte sheet. If the mass exceeds 2.5 g, the Li₂O atmosphere becomes too concentrated, potentially generating reducing properties and leading to the formation of ZrO₂ impurities.

[0017] Preferably, the solid electrolyte mother powder coated solid electrolyte sheet is sintered at a sintering temperature of 1200° C. to 1400° C. for 8 h to 12 h at a heating rate of 2° C. / min to 5° C. / min.

[0018] The heating rate is controlled between 2°C / min and 5°C / min to control the lithium volatilization rate. This rate matches the volatilization rate of Li₂O with the internal ion diffusion rate, avoiding localized lithium depletion. Furthermore, the sintering temperature is controlled between 1200°C and 1400°C to promote grain refinement and density while suppressing lithium volatilization. This temperature range results in high surface energy for the raw material particles, where the nucleation rate exceeds the growth rate, promoting grain refinement. Furthermore, at high temperatures, pores between particles fill through surface diffusion and grain boundary diffusion, resulting in a density exceeding 95%. When the sintering temperature is below 1200°C, the powder remains amorphous or semicrystalline, ion conduction relies on defect diffusion, and electrical conductivity is low. When the sintering temperature is above 1400°C, the Li₂O volatilization rate reaches as high as 15%-20%, and rapid grain growth squeezes out grain boundary pores, forming a closed-pore structure, causing the density to drop below 90%. The sintering time is controlled between 8 and 12 hours to ensure complete formation of sintering necks between particles while preventing excessive grain growth. This time allows the sintering necks between the raw material particles to fully develop, the proportion of bulk resistance to decrease, the proportion of grain boundary resistance to increase, the total impedance to decrease, and the ionic conductivity to increase. When the sintering time is less than 8h, the sintering necks between the particles are not fully formed, the proportion of bulk resistance to decrease, the proportion of grain boundary resistance to increase, the total impedance to increase, and the density of the electrolyte sheet to be low. When the sintering time is greater than 12h, stress concentration occurs at the grain boundaries, microcracks appear in the sintered body, and excessive lithium volatilization causes Li in the lattice to + The conduction path is broken and the conductivity decreases.

[0019] Preferably, filtering is performed using a 200 mesh screen.

[0020] A 200-mesh screen is used for filtration because it can retain larger particles. These coarse particles are often aggregates of raw materials that have not been fully ball-milled. If mixed with masterbatch, they can lead to inconsistent local densification during sintering and form pores. Sieving the powder ensures uniform particle packing during tableting and improves grain size consistency after sintering.

[0021] The invention provides a method for preparing a solid electrolyte and obtains a garnet-type solid electrolyte.

[0022] Preferably, the particle size of the garnet-type solid electrolyte is 5 μm to 10 μm.

[0023] At the same time, the refined grains (5μm~10μm) reduce the number of grain boundaries, and the high density reduces the porosity, making ions (such as Li + ) is easier to conduct through the lattice or grain boundary, optimizing and reducing the transmission barrier. At the same time, this method inhibits lithium volatilization and ensures that Li + The concentration is stable, maintaining the smoothness of the ion conduction channel, and the lithium content is also stable to maintain the integrity of the lattice.

[0024] Preferably, the garnet-type solid electrolyte is tantalum-doped Li 6.5 La3Zr 1.5 Ta 0.5 O 12 or Al-doped Li 6.28 Al 0.24 La3Zr2O 12 .

[0025] Compared with the prior art, the present invention has the following beneficial effects: The solid electrolyte preparation method provided by the present invention uses a high-temperature solid-phase sintering method, a layered electrolyte sheet coating method, and a double-layer crucible sintering method to prepare the solid electrolyte. The high-temperature solid-phase sintering method can refine the grains and improve the density of the electrolyte. The porous MgO crucible inside the double-layer crucible is highly stable and does not react with the Li2O in the solid electrolyte raw material. The dense Al2O3 crucible on the outer layer can provide good sealing, prevent raw material volatilization, and improve the performance of the solid electrolyte. The layered electrolyte sheet coating method can improve sintering efficiency. This is because:

[0026] In the solid-state electrolyte preparation method provided by the present invention, isopropyl alcohol (C3H8O) is used for ball milling with the raw materials for preparing the solid-state electrolyte because the isopropyl group in its molecular structure is more hydrophobic. In addition, isopropyl alcohol is slightly less volatile than ethanol, which can reduce solvent loss during the ball milling process. Compared with other solvents, isopropyl alcohol is a secondary alcohol, and the acidity and electrophilicity of the –OH group are weaker than those of methanol / ethanol. The steric effect makes it more difficult for protons to insert into the LLZTO framework, significantly reducing the proton exchange rate. Isopropyl alcohol, as a low-viscosity liquid, can fill the gaps between the ball milling beads and the particles. When the ball milling beads collide, the liquid medium evenly transfers the impact force to the particle surface, avoiding local stress concentration and resulting damage to the crystal structure.

[0027] When sintered by high-temperature solid-phase sintering, the surface energy of the fine particles is high, and the nucleation rate is greater than the growth rate, which promotes grain refinement and reduces the atomic diffusion distance, reducing the driving force for grain growth, and avoiding grain coarsening due to long-term sintering at high temperature. Moreover, during the sintering process, the fine particles fill the pores through surface diffusion, grain boundary diffusion, etc. at high temperature, increasing the contact area between particles, reducing the porosity, and improving the density of the solid electrolyte.

[0028] In addition, the preparation method of the solid electrolyte provided by the present invention provides a coating method to coat the solid electrolyte mother powder layer by layer on 2 to 4 solid electrolyte sheets from bottom to top, and cap it with solid electrolyte mother powder. This layered electrolyte sheet coating method can improve the sintering efficiency. This is because when each layer of solid electrolyte mother powder wraps the electrolyte sheet, an alternating structure of "mother powder-sheet-mother powder" is formed. During sintering, the mother powder can inhibit the decomposition of the electrolyte sheet. Moreover, the layer-by-layer coating significantly increases the contact area between the mother powder and the electrolyte sheet (compared to traditional single-layer sintering), accelerates the atomic diffusion rate at the interface, promotes dense bonding between layers, and reduces grain boundary resistance. Using crucible stacking to coat the electrolyte sheet for sintering can make more full use of the mother powder, make the crucible space utilization higher, thereby reducing the volatilization and waste of the mother powder, maximizing the interface contact area, and thus improving the sintering efficiency.

[0029] At the same time, the refined grains reduce the number of grain boundaries, while the high density reduces the porosity, both of which make it easier for lithium ions to conduct through the lattice or grain boundaries, optimizing and reducing transmission obstacles. At the same time, this method inhibits lithium volatilization and ensures that Li in the electrolyte lattice + The concentration is stable, maintaining the smoothness of the ion conduction channel, and the lithium content is also stable to maintain the integrity of the lattice.

[0030] The present invention utilizes a double-layer crucible to improve sealing performance, a result of the synergistic effect of its structural design and material properties. A porous MgO crucible is used for the inner layer because MgO, an alkali metal oxide, does not react with the Li₂O produced by the decomposition of the electrolyte raw materials, thus preventing the continued decomposition of the electrolyte sheet. A dense Al₂O₃ crucible is used for the outer layer because Al₂O₃ has a high density and low thermal conductivity, forming a physical sealing barrier to prevent the diffusion of Li₂O gas. Furthermore, its high-temperature resistance (melting point 2054°C) ensures structural stability at sintering temperatures, maintaining a good seal.

[0031] The use of a double-layer crucible also suppresses lithium volatilization. This is because lithium easily volatilizes as Li2O gas at high temperatures, causing electrolyte decomposition. The double-layer crucible provides a dual barrier and seal. The stable porous MgO crucible prevents other elements from diffusing into the electrolyte sheet at high temperatures. The dense Al2O3 layer creates a relatively closed sintering environment, preventing the escape of Li2O gas and maintaining electrolyte stability.

[0032] The solid electrolyte prepared by the solid electrolyte preparation method provided by the present invention has high lithium ion conductivity (σ Li+ =9.67×10 -4 S / cm) and excellent chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the MgO-Al2O3 double-layer crucible used in the present invention.

[0034] Figure 2 This is a cross-sectional scan of the electrolyte sheet after sintering in Example 1.

[0035] Figure 3 This is a cross-sectional scan of the electrolyte sheet after sintering in Control Example 1.

[0036] Figure 4 This is a cross-sectional scan of the electrolyte sheet after sintering in Control Example 2.

[0037] Figure 5 This is the AC impedance spectrum measured when the electrolyte sheet obtained in Example 1 is assembled into a lithium symmetrical battery. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned purposes, features and advantages of the embodiments of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0039] The inventors discovered that the traditional garnet-type solid electrolyte preparation process (such as the high-temperature solid-phase method) has significant defects in the sintering process: when the sintering temperature exceeds 1200°C, the electrolyte composition will deviate from the stoichiometric ratio due to the violent volatilization of lithium elements (the volatilization amount is as high as 15%~20%), and the porosity at the grain boundaries will increase, resulting in a density of less than 85%, which ultimately leads to a significant decrease in ion transmission efficiency. In addition, a single material crucible (such as MgO or Al2O3) cannot solve the problems of lithium volatilization and sintering environment stability at the same time. Although a single MgO crucible has high chemical stability, its lack of density makes Li2O gas easy to escape; although a single Al2O3 crucible has good sealing, during the high-temperature sintering process, Al2O3 will not be able to withstand high temperatures. 3+ It will diffuse into the electrolyte sheet, affecting the product composition deviation. Traditional single-layer stacking results in uneven distribution of lithium sources during sintering, further exacerbating the composition differences and performance fluctuations within the electrolyte sheet.

[0040] In view of this, the present invention provides a solid electrolyte and a preparation method thereof, aiming to solve the problems raised in the technical background. The solid electrolyte preparation method refines the grains and grain density, avoids the volatilization of lithium elements, and improves the ion transmission efficiency.

[0041] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Since the steps and methods used are the same as those in Examples 1 to 5, in order to avoid redundancy, the present invention describes a preferred embodiment, but the present invention is not limited thereto, but can also be specifically implemented in other ways within the scope of the technical solution defined in the attached claims.

[0042] The technical solution of the present invention is further illustrated below in the form of specific examples.

[0043] The garnet-type solid electrolyte can be tantalum-doped Li 6.5 La3Zr 1.5 Ta 0.5 O 12 or Al-doped Li 6.28 Al 0.24 La3Zr2O 12 Therefore, the embodiment of the present invention is to prepare Li 6.5 La3Zr 1.5 Ta 0.5 O 12 Expand, the crucible used in the following examples is as follows Figure 1 shown.

[0044] Example 1 A method for preparing a solid electrolyte comprises the following steps: 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm were mixed with the prepared Li 6.5 La3Zr 1.5 Ta 0.5 O 12 The raw materials LiOH, La2O3, ZrO2 and Ta2O5 are placed in a ball mill, and are milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, the powder is transferred to a MgO crucible, placed in a muffle furnace, and heated to 900°C at a rate of 5°C / min for sintering for 10 hours. The sintered powder is again placed in a ball mill containing 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm. The powder is milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, it is sieved through a 200-mesh sieve to obtain a solid electrolyte mother powder.

[0045] Weigh 1.2 g of solid electrolyte mother powder and put it into a tablet pressing mold. Press at a pressure of 300 MPa for 5 minutes to obtain a solid electrolyte green sheet. Three solid electrolyte green sheets were layered in a MgO-Al2O3 double-layer crucible using 2.1g, 1.4g, 1.4g, and 1.4g of solid electrolyte mother powder, respectively. The crucible was then covered with a MgO-Al2O3 double-layer lid. The crucible was then placed in a muffle furnace and heated to 1200°C at a rate of 5°C / min and sintered for 10 hours.

[0046] After sintering, the solid electrolyte is obtained by cutting, grinding and polishing using a wire cutting machine.

[0047] Example 2 A method for preparing a solid electrolyte comprises the following steps: Ten large ball milling beads with a diameter of 14 mm and 80 small ball milling beads with a diameter of 8 mm were mixed with the prepared Li 6.5 La3Zr 1.5 Ta 0.5 O 12 The raw materials LiOH, La2O3, ZrO2 and Ta2O5 are placed in a ball mill, and are milled for 5 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, the powder is transferred to a MgO crucible, placed in a muffle furnace, and heated to 700°C at a rate of 2°C / min for sintering for 8 hours. The sintered powder is again placed in a ball mill containing 10 large ball milling beads with a diameter of 14 mm and 80 small ball milling beads with a diameter of 8 mm. The powder is milled for 5 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, it is sieved through a 200-mesh sieve to obtain a solid electrolyte mother powder.

[0048] Weigh 1.0 g of solid electrolyte mother powder and place it in a tablet pressing mold at a pressure of 200 MPa for 5.5 min to obtain a solid electrolyte green sheet; Three solid electrolyte green sheets were layered in a MgO-Al2O3 double-layer crucible using 2.1g, 1.4g, 1.4g, and 1.4g of solid electrolyte mother powder, respectively. The crucible was then covered with a MgO-Al2O3 double-layer lid. The crucible was then placed in a muffle furnace and heated to 1300°C at a rate of 2°C / min and sintered for 8 hours.

[0049] After sintering, the solid electrolyte is obtained by cutting, grinding and polishing using a wire cutting machine.

[0050] Example 3 A method for preparing a solid electrolyte comprises the following steps: Fifteen large ball milling beads with a diameter of 10 mm and 60 small ball milling beads with a diameter of 4 mm were mixed with the prepared Li 6.5 La3Zr 1.5 Ta0.5 O 12 The raw materials LiOH, La2O3, ZrO2 and Ta2O5 are placed in a ball mill, and are milled for 15 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, the powder is transferred to a MgO crucible, placed in a muffle furnace, and heated to 1000°C at a rate of 3°C / min and sintered for 12 hours. The sintered powder is again placed in a ball mill containing 15 large ball milling beads with a diameter of 10 mm and 60 small ball milling beads with a diameter of 4 mm. The powder is milled for 15 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, it is sieved through a 200-mesh sieve to obtain a solid electrolyte mother powder.

[0051] Weigh 1.3 g of solid electrolyte mother powder and place it in a tablet pressing mold. Press at a pressure of 400 MPa for 6 minutes to obtain a solid electrolyte green sheet. Three solid electrolyte green sheets were layered in a MgO-Al2O3 double-layer crucible using 2.1g, 1.4g, 1.4g, and 1.4g of solid electrolyte mother powder, respectively. The crucible was then covered with a MgO-Al2O3 double-layer lid. The crucible was then placed in a muffle furnace and heated to 1400°C at a rate of 3°C / min and sintered for 12 hours.

[0052] After sintering, the solid electrolyte is obtained by cutting, grinding and polishing using a wire cutting machine.

[0053] Example 4 The only difference between Example 4 and Example 1 is that 2.1 g, 1.0 g, and 1.0 g of solid electrolyte mother powder are used to coat two solid electrolyte green sheets layer by layer in a MgO-Al2O3 double-layer crucible, respectively.

[0054] Example 5 The only difference between Example 4 and Example 1 is that 2.5 g, 1.0 g, 1.0 g, 1.0 g and 1.0 g of solid electrolyte mother powder are used to coat four solid electrolyte green sheets layer by layer in a MgO-Al2O3 double-layer crucible, respectively.

[0055] Comparative Example 1 A method for preparing a solid electrolyte comprises the following steps: 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm were mixed with the prepared Li 6.5 La3Zr 1.5 Ta 0.5 O 12The raw materials LiOH, La2O3, ZrO2 and Ta2O5 are placed in a ball mill, and are milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, the powder is transferred to a crucible, placed in a muffle furnace, and heated to 900°C at a rate of 5°C / min for sintering for 10 hours. The sintered powder is again placed in a ball mill containing 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm. The powder is milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, it is sieved through a 200-mesh sieve to obtain a solid electrolyte mother powder.

[0056] Weigh 1.2 g of solid electrolyte mother powder and put it into a tablet pressing mold. Press at a pressure of 300 MPa for 5 minutes to obtain a solid electrolyte green sheet. 0.7 g of solid electrolyte mother powder was used to coat a solid electrolyte sheet on top and bottom in a ZrO2 crucible, which was then covered. The crucible was then placed in a muffle furnace and heated to 1200°C at a rate of 5°C / min and sintered for 10 hours.

[0057] Comparative Example 2 A method for preparing a solid electrolyte comprises the following steps: 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm were mixed with the prepared Li 6.5 La3Zr 1.5 Ta 0.5 O 12 The raw materials LiOH, La2O3, ZrO2 and Ta2O5 are placed in a ball mill, and are milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, the powder is transferred to a crucible, placed in a muffle furnace, and heated to 900°C at a rate of 5°C / min for sintering for 10 hours. The sintered powder is again placed in a ball mill containing 20 large ball milling beads with a diameter of 12 mm and 40 small ball milling beads with a diameter of 6 mm. The powder is milled for 10 hours using a planetary ball mill with isopropyl alcohol as the ball milling agent. After drying with air at 70°C, it is sieved through a 200-mesh sieve to obtain a solid electrolyte mother powder.

[0058] Weigh 1.2 g of solid electrolyte mother powder and place it in a tablet pressing mold. Press at a pressure of 300 MPa for 5 minutes to obtain a solid electrolyte green sheet. 0.7 g of solid electrolyte mother powder was used to coat a solid electrolyte sheet on top and bottom in a porous MgO crucible, which was then covered. The crucible was then placed in a muffle furnace and heated to 1200°C at a rate of 5°C / min and sintered for 10 hours.

[0059] The above-mentioned Examples 1 to 5 can all prepare solid electrolytes. The following experiments are conducted using the solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0060] Experimental verification of the present invention: Experimental verification of the present invention: (3) SEM images like Figure 2 The solid electrolyte prepared using a double-layer crucible exhibits a typical fine-grained structure, with grain sizes uniformly distributed within the 5μm to 10μm range, clear grain boundaries, and no significant residual pores. The density is calculated to exceed 95%. Microscopic morphology reveals close contact between grain boundaries and well-developed sintering necks, indicating that double-layer crucible sintering effectively promotes interparticle diffusion and densification. This uniformly refined microstructure provides continuous crystal channels for lithium-ion transport, a crucial microscopic foundation for its high ionic conductivity. Figure 3 and Figure 4 The grain size is uneven, with obvious pores visible at the grain boundaries. Lithium volatilization has led to the formation of honeycomb-like pores in local areas, and the density is only about 82%. The raw material particles are severely agglomerated, and the grain boundaries are blurred after sintering. There are incompletely fused particle interfaces, which hinder ion transmission paths.

[0061] (4) AC impedance spectroscopy The ionic conductivity σ of the solid electrolyte in Experimental Example 1 was obtained by calculation. Li+ =9.67×10 -4 S / cm (such as Figure 5 As shown in Figure 2), it is of great significance in many aspects: compared with traditional materials, the ionic conductivity of garnet-type solid electrolytes is usually around 10 -4 S / cm level, which is close to or reaches the level of high-quality garnet electrolyte, indicating that the preparation process (double-layer crucible, mother powder layer coating) effectively improves the density of the solid electrolyte.

[0062] Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, if such modifications and variations fall within the scope of the claims and their equivalents, the present invention is intended to include such modifications and variations.

Claims

1. A method for preparing a solid electrolyte, characterized in that: The steps include: Isopropyl alcohol is added as a ball milling agent to raw materials for preparing a tantalum-doped solid electrolyte or an aluminum-doped solid electrolyte, and ball milling is performed. The ball-milled powder is dried to obtain a dry mixed powder. The dry mixed powder is placed in an MgO crucible for sintering. Isopropyl alcohol is added to the sintered product, and the product is ball milled again, dried, and sieved to obtain a solid electrolyte mother powder. Pressing the prepared solid electrolyte mother powder into tablets to obtain solid electrolyte green sheets; In a MgO-Al2O3 double-layer crucible, the solid electrolyte mother powder is coated layer by layer on 2 to 4 solid electrolyte green sheets from bottom to top by using the coating method, and the top is sealed with the solid electrolyte mother powder to obtain a layered coating; The layered coating is sintered, divided after sintering, and then ground and polished to obtain a solid electrolyte; The inner layer of the MgO-Al2O3 double-layer crucible is a porous MgO crucible, and the outer layer of the double-layer crucible is an Al2O3 crucible.

2. The method for preparing a solid electrolyte according to claim 1, wherein: Place 10 to 20 large ball milling beads with a diameter of 10 mm to 14 mm, 40 to 80 small ball milling beads with a diameter of 4 mm to 8 mm, and the raw materials for preparing the solid electrolyte into a ball milling jar, use isopropyl alcohol as a ball milling agent, and ball mill for 5 hours to 15 hours.

3. The method for preparing a solid electrolyte according to claim 1, wherein: The dried powder is sintered at a sintering temperature of 700°C to 1000°C for 8h to 12h at a heating rate of 2°C / min to 5°C / min.

4. The method for preparing a solid electrolyte according to claim 1, wherein: The conditions for pressing the solid electrolyte mother powder to obtain the solid electrolyte sheet are as follows: 1.0g~1.3g of the mother powder is pressed under a pressure of 200Mpa~400Mpa for 5min~6min to obtain the solid electrolyte sheet.

5. The method for preparing a solid electrolyte according to claim 1, wherein: The mass of each layer of solid electrolyte mother powder wrapped solid electrolyte sheet is 1.0g~2.5g.

6. The method for preparing a solid electrolyte according to claim 1, wherein: The solid electrolyte mother powder coated solid electrolyte sheet is sintered at a sintering temperature of 1200° C. to 1400° C. for 8 h to 12 h at a heating rate of 2° C. / min to 5° C. / min.

7. The method for preparing a solid electrolyte according to claim 1, wherein: Filter through a 200-mesh sieve.

8. The garnet-type solid electrolyte obtained by the method for preparing a solid electrolyte according to any one of claims 1 to 7.

9. The garnet-type solid electrolyte prepared by the method for preparing a solid electrolyte according to claim 8, characterized in that: The particle size of the garnet-type solid electrolyte is 5 μm to 10 μm.

10. The garnet-type solid electrolyte prepared by the method for preparing a solid electrolyte according to claim 8, characterized in that: Garnet-type solid electrolyte is tantalum-doped Li 6.5 La3Zr 1.5 Ta 0.5 O 12 or Al-doped Li 6.28 Al 0.24 La3Zr2O 12 .